Increase in liana prevalence after logging and thinning in an eastern Amazonian forest - Slätis, Johan; Auranen, Kari; Tuomisto, Hanna; do Nascimento Clementino; José Bruno; Mazzei de Freitas; Lucas José (ELSEVIER, 2026)
Sustainability of forestry relies on the recovery of forest structure and timber stocks after logging. Canopy gaps created by logging often lead to liana proliferation, which can reduce forest productivity and reduce global CO2 sequestration. Using inventory data from Brazil's Tapajos National Forest, we examined changes in liana prevalence (proportion of trees with lianas) following selective logging and thinning. Prevalence increase was proportional to the reduction of tree basal area (BA), measured from 12 ha of logged and 9 ha of subsequently thinned inventory plots. Following a 24 % BA reduction, liana prevalence doubled within seven years after logging and thereafter remained elevated throughout the 20-year study period. Twelve years after logging, 3/4 of the plots were thinned of non-commercial species by girdling. Annual increase in liana prevalence was similar (c. 2 percentage points per year, %pts/yr) in the immediate years after both logging and thinning. However, after thinning, for each additional m2/ha of basal area reduction, the increment in annual increase of liana prevalence was four times larger than after logging (0.28 vs. 0.06 %pts/yr). Thinning occurred before forest structure had recovered to mid-and top-canopy closure, and leaving the liana vegetation intact led to a more intense increase in liana prevalence than had occurred after the initial logging. Our results suggest that thinning by girdling may not effectively liberate future crop trees, unless combined with ecologically sound suppression of excessive liana growth. Adequate forest recovery time appears necessary to prevent recurring liana increases after successive logging cycles and thinning.